2014
DOI: 10.1136/jech-2013-203306
|View full text |Cite
|
Sign up to set email alerts
|

Income-related inequality in health and health-related behaviour: exploring the equalisation hypothesis

Abstract: BackgroundPrevious studies have found the socioeconomic gradient in health among adolescents to be lower than that observed during childhood and adulthood. The aim of this study was to examine income-related inequalities in health and health-related behaviour across the lifespan in England to explore ‘equalisation’ in adolescence.MethodsWe used five years of data (2006–2010) from the Health Survey for England to explore inequalities in six indicators: self-assessed general health, longstanding illness, limitin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 38 publications
1
31
0
1
Order By: Relevance
“…The only reduction in inequality was found for SED, although social differences remained substantial at 11 years. Recent research highlighted previously has indicated that equalisation may be shifting to later adolescence 8. This should be further assessed as the MCS participants enter mid and late adolescence.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The only reduction in inequality was found for SED, although social differences remained substantial at 11 years. Recent research highlighted previously has indicated that equalisation may be shifting to later adolescence 8. This should be further assessed as the MCS participants enter mid and late adolescence.…”
Section: Discussionmentioning
confidence: 94%
“…However, the majority of research has documented inequalities in children at single points in time. Although there is evidence of a possible period of equalisation during adolescence,8 this has largely been based on cross-sectional data and much less is known about how population-level health inequalities change in the same group of children as they age throughout childhood. Cohort data would improve our understanding of how health inequalities develop over this important period of the life course and whether patterns vary for different aspects of health.…”
Section: Introductionmentioning
confidence: 99%
“…There are substantial social inequalities in oral health, with children from disadvantaged and ethnic minority backgrounds experiencing poorer oral health . Furthermore, there is considerable evidence that socioeconomic health inequalities appear to reduce from childhood to adolescence leading to the hypothesis of social equalization during adolescence . This hypothesis involves a change in the pattern of socioeconomic differences in health from 1 in childhood characterized by health inequalities to 1 in youth characterized by relative equality .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the present results cannot be generalized to all late‐stage older individuals. Socioeconomic factors, such as economic status and educational level, significantly affect health behaviors, including the use of medical institutions . In a study that examined the relationship between the number of teeth and the medical costs of stroke for those aged 80 years, income and education years did not show significant influences .…”
Section: Discussionmentioning
confidence: 99%